Comfort in plus size clothing: user-focused innovation and textile technology (ModaPalavra e-periódico, 2022)
Plus size clothing products must meet aspects related to body comfort. Thus, the relevance of this study lies in the needs highlighted by the consumer related to comfort, as well as in the dissemination of research on social diversity. Its objective is to present innovative clothing alternatives, based on the requirements for the development of plus size products, which, through textile technology, guarantee greater comfort to the consumer. It is a research of a basic nature, qualitative in terms of approach to the problem and descriptive in terms of objectives, with a theoretical basis on books and scientific works. The present study brings results - such as the proposal of innovative products developed through the creation and application of a hybrid methodology for the creation of new products - which, through specific materials and production processes, can meet the comfort needs of the plus size consumer.
Keywords: Comfort; Clothing; Textile Technology